Plan de Negocios para el sistema Web SoilDrones Orientado al análisis de suelos, Generación de informes y Almacenamiento de Historial (2016)
Soildrones is a set of integrated services which seeks to innovate in the field of agriculture in Colombia integrating new technologies such as drones and image recognition. Soildrones focuses on one of the most important processes in agriculture that is "soil analysis" in which we currently work in a very traditional way and this entails certain variations and inaccuracies in the results that are collected. Soildrones to attack this problem offers a service of sampling of high precision, together with an accompaniment of personnel expert in the subject and a web platform that allows the user to have a traceability over the time of the evolution of their lands.